(untitled) (FAVE Sección Ciencias Veterinarias, 2022)
In the last 4 years, Uruguay has experienced a growing demand of raw fish-based foods, such as sushi, sahimi and ceviche. This scenario generated the need to assess the presence and concentration of zoonotic parasites (Nematodoes: Anisakidae) in edible parts of fish species traded in the local market. 233 fish specimens of 3 species commercialized in Uruguay were analyzed: Macrodon ancylodon, Micropogonias furnieri and Cynoscion guatucupa. The nematodes were quantified and identified at genus level, from coelomic cavity and muscle of the fishes, to finally stablish the ecological descriptors for each genus founded and for each fish species evaluated. Two of the three species of fish were parasitized with anisakids in both location (coelomic cavity and muscle), M. ancylodon and C. guatucupa. C. guatucupa was the most parasitized with a prevalence of 46%, while, the anisakid genus most prevalente was Contracaecum (prevalence of 35,1% in C. guatucupa and 32,4% in M. ancylodon). The finding of anisakids in M. ancylodon represents a report of a new host in Uruguay. Moreover, the finding for the first time in the country of these zoonotic parasites in edible parts of fish (muscle) is highlighted.